Constructing Twenty-First Century Socialism in Latin America The Role of Radical Education - Motta, Sara C.; Cole, Mike.; SpringerLink (Online service) (New York : Palgrave Macmillan US : Imprint: Palgrave Macmillan, 2014)
Mike Cole and Sara Motta explore the role of radical education in constructing twenty-first century socialism in Latin America, focusing on Venezuela, Bolivia, Brazil, and Mexico. .
Keywords: Science; Science; Science, general